PEMBUATAN KOMPOS BAGI GURU DAN ORANG TUA MURID TK. QURRATA A’YUN DI CIMAHI - Nurhuda, Tiara; Abdul Muluk, R. Kiki; Bhagya, Tombak Gapura; Murdikaningrum, Galu (LPPM IST AKPRIND Yogyakarta, 2021)
There are so many resources but cannot be utilized optimally. One example that is familiarwith our lives is household waste. This waste can be used as fertilizer but can also berecycled as an improvement in the community's economy, its management is very easy andsimple. Organic waste in the form of leaves, stems of plants that can be processed aerobicand anaerobic in composter produce organic fertilizer called compost. This research usesthe method of mixing ingredients in a composter by using the EM4 microbe as an activator.The results of this study indicate that goat manure has an effect on speeding up the processof compost. It is shown by the change in color and maturity of the compost at 25oC –30oCon the 21st day.